Seizure activity and brain damage in a model of focal non‐convulsive status epilepticus. (27th January 2021) - Vila Verde, Diogo; Zimmer, Till; Cattalini, Alessandro; Pereira, Marlene F.; van Vliet, Erwin A.; Testa, Giuseppe; Gnatkovsky, Vadym; Aronica, Eleonora; de Curtis, Marco
Abstract: Aims: Focal non‐convulsive status epilepticus (FncSE) is a common emergency condition that may present as the first epileptic manifestation. In recent years, it has become increasingly clear that de novo FncSE should be promptly treated to improve post‐status outcome. Whether seizure activity occurring during the course of the FncSE contributes to ensuing brain damage has not been demonstrated unequivocally and is here addressed. Methods: We used continuous video‐EEG monitoring to characterise an acute experimental FncSE model induced by unilateral intrahippocampal injection of kainic acid (KA) in guinea pigs. Immunohistochemistry and mRNA expression analysis were utilised to detect and quantify brain injury, 3‐days and 1‐month after FncSE. Results: Seizure activity occurring during the course of FncSE involved both hippocampi equally. Neuronal loss, blood‐brain barrier permeability changes, gliosis and up‐regulation of inflammation, activity‐induced and astrocyte‐specific genes were observed in the KA‐injected hippocampus. Diazepam treatment reduced FncSE duration and KA‐induced neuropathological damage. In the contralateral hippocampus, transient and possibly reversible gliosis with increase of aquaporin‐4 and Kir4.1 genes were observed 3 days post‐KA. No tissue injury and gene expression changes were found 1‐month after FncSE. Conclusions: In our model, focal seizures occurring during FncSE worsen ipsilateral KA‐induced tissue damage. FncSE only transiently activated glia in regions remote from KA‐injection, suggesting that seizure activity during FncSE without local pathogenic co‐factors does not promote long‐lasting detrimental changes in the brain. These findings demonstrate that in our experimental model, brain damage remains circumscribed to the area where the primary cause (KA) of the FncSE acts. Our study emphasises the need to use antiepileptic drugs to contain local damage induced by focal seizures that occur during FncSE. Abstract : Seizures during NCSE worsen damage at the site of KA injection, but do not damage remote regions, such as the contralateral hippocampus where no cell loss or BBB damage was present and a transient and likely protective gene up‐regulation and microglial morphometric changes were observed.